Manajemen Pendidikan Agama Islam: Studi Pembelajaran Membaca al-Qur’an dengan Metode Qiroati di Sekolah Dasar Islam Terpadu Sabilul Huda - Novianti Muspiroh (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2020)
Qur’an is a guide to life. Reading it is worship, so the ability to read the Qur'an correctly, within the scope of Islamic religious education, is an important ability, students should master it.  This capability is continuously being developed in Islamic Primary Full Day School Sabilul Huda Cirebon City. This study aimed to reveal in-depth the management of learning to read Qur’an with the Qiroati method in Islamic Primary Full Day School Sabilul Huda Cirebon City. This research was a field qualitative case study research. Data collection instruments were in-depth observation, in-depth interviews, and documentation. Analysis techniques were carried out through data collection, data reduction, data presentation, and data conclusions. The results showed that: (1) Qiroati learning planning was done carefully starting from teacher preparation, learning methods, learning time, learning targets, and teaching aids. (2) The Qiroati Learning used individual methods, individual classics, classical reading, drill, writing, and reading. Each class was guided by a Qiroati teacher.(3) Evaluation of Qiroati learning was carried out through daily evaluation, upgrading evaluation, and final evaluation.